ia2sp10h9s

# ∞ x n =1 ˜ ‘ k n = lim n →∞ n x k =1 f d k 1

This preview shows pages 4–6. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ∞ X n =1 ˜ ‘ ( K n ) = lim n →∞ n X k =1 ( f ( d k +1 )- f ( d k )) = lim n →∞ f ( d n +1 )- f ( d 1 ) = f ( b- )- f ( d 1 ) . ˜ ‘ ( H ) = f ( d 1 )- f ( c 1 ) . ∞ X n =1 ˜ ‘ ( L n ) = ∞ X n =1 f c n + δ n 2 ¶- f c n- δ n 2 ¶¶ < ∞ X n =1 e 2 n +1 = ² 2 . ∞ X n =1 ˜ ‘ ( M n ) = ∞ X n =1 ‡ f ‡ d n + η n 2 ·- f ‡ d n- η n 2 ·· < ∞ X n =1 e 2 n +1 = ² 2 . Because we have a countable cover of I , the sum of the expressions on the left of the first of all these equali- ties/inequalitites dominates μ * ( I ); adding up we thus get μ * ( I ) < f ( b- )- f ( a +) + ². Since ² > 0 is arbitrary, μ * ( I ) ≤ f ( b- )- f ( a +) follows, establishing Claim 2. Claim 3. If I = ( a,b ],-∞ ≤ a < b < ∞ , then (7) μ * ( I ) = f ( b +)- f ( a +) Assume first that a > ∞ . We can proceed exactly as we did in proving the first inequality in (4), with two difference. The countable cover { J n } is defined in the same way in terms of ² , but then we use the fact that [ a + η,b ] is compact to extract a finite subcover of [ a + η,b ]. That is the first difference; that b- η does not appear; it is replaced by b . The second difference is that where we used f ( b- η ) ≤ f ( d n k ), now we use that f ( b +) ≤ f ( d n k ). Everything else is the same, and we end with μ * ( I ) ≥ f ( b +)- f ( a +). For the converse of this inequality, select any c ∈ ( a,b ) at which f is continuous. For a small δ consider the open intervals ( a,c ) , ( c- δ,c + d ) , ( c,b + δ ). These intervals cover I ; because μ * is an outer measure and by Claim 2: μ * ( I ) ≤ μ * (( a,c ))+ μ * (( c- δ,c + δ ))+ μ * (( c,b + δ )) = f ( c- )- f ( a +)+ f (( c + δ )- )- f (( c- δ )+)+ f (( b + d )- )- f ( c +) . Using the continuity of f at c , letting δ → 0, we get μ * ( I ) ≤ f ( b +)- f ( a +), establishing Claim 3 . With this we can return to where we were on hold, namely at (3). With the notation as defined there, we have (8) μ * ( I 1 n ) + μ * ( I 2 n ) = μ * ( I n ) = f ( b n- )- f ( a n +) 4 for all n ∈ N . (The last equality is, of course, just claim 2). Let I n = ( a n ,b n ). If one of I 1 n ,I 2 n is empty, then the other one is I n and (8) is trivially true. Otherwise, a n < a < b n and I 1 n = ( a,b n ), I 2 n = ( a n ,a ] and by claims 2, 3 μ * ( I 1 n ) + μ * ( I 2 n ) = f ( b n- )- f ( a +) + f ( a +)- f ( a n +) = f ( b n- )- f ( a n +) as asserted. Now f ( b n- )- f ( a n +) ≤ f ( b n )- f ( a n ) ˜ ‘ ( I n ) so that (3) and (8) imply μ * ( A 1 ) + μ * ( A 2 ) ≤ ∞ X n =1 ˜ ‘ ( I n ) , completing the proof of (2). This concludes the treatment of part (b), except for a some comments. Borel sets are measurable. Not every countable or even finite set has measure zero in this model. For example, if f has a jump at c , then from μ * (( c- ²,c ]) = f ( c +)- f ( c- ² +) it is quite easy to deduce that μ * ( { c } ) = f ( c +)- f ( c- ) ....
View Full Document

{[ snackBarMessage ]}

### Page4 / 7

∞ X n =1 ˜ ‘ K n = lim n →∞ n X k =1 f d k 1 f d k...

This preview shows document pages 4 - 6. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online